Implementasi Pembelajaran Inovatif Berbasis Proyek Sebagai Upaya Peningkatan Kemampuan Siswadi Sekolah Dasar - Miftachul Amri; Dyah Worowirastri Ekowati; Fitria Febriyanti (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2023)
Learning outcomes are a person's change in the learning process so as to achieve self-change after the learning process. Mathematics learning outcomes can be achieved if students reach the aspects that are assessed and succeed by showing changes in themselves as a result of cognitive mathematics learning outcomes. Learning material is an outline of the knowledge, skills, and attitudes that students must achieve in order to learn to certain competency standards. Flat shapes are two-dimensional geometric objects having various shapes such as squares, rectangles, triangles, circles, parallelograms, and trapezoids. Project-based learning, or PBL, is learning that uses an activity model in the form of a project or activity, which is a medium of learning. The characteristics of successful mathematics learning in achieving competence are flexible learning tools, especially learning models that have effective, efficient, and useful principles as the key to success in learning mathematics. In flat-shaped materials, the appropriate learning model is project-based learning because the media in project-based learning are activities. The purpose of this study was to determine the learning achievement of IC class students at SDN Purwantoro 1, Malang City, in mathematics by utilizing the project-based learning model. The research participants were 28 students in my IC class. The data collected are the results of the pretest and evaluation results at each meeting. The results of the study state that the application of the project-based learning (PJBL) learning model can make it easier for students to understand the material seen during the learning process and the learning outcomes.